Natural Rights, Human Rights, and Libertarianism. (January 2015) - Block, Walter E.
Abstract The present article is devoted to developing a libertarian understanding of whether natural rights may or may not underpin human rights and, if so, how. Libertarianism is first defined in terms of the nonaggression principle (NAP), in answer to the question "What is the proper use of force?" This provides a basis for the libertarian positions on property rights, taxation, and many other issues, including human rights. Various philosophical rationales for the NAP are explored, including utilitarianism, religion, and natural rights. The basis of human rights is then examined. Every ethical tradition supports the nonaggression principle, which makes it an ideal candidate for the fundamental basis of human rights. Unfortunately, other traditions expand upon human rights by adding "positive" rights that ultimately violate the NAP. The conclusion takes up the application of libertarian principles to three issues, which could be viewed as human rights questions: discrimination, abortion, and the "trolley problem." The last one involves taking one life to save many others.